2018
DOI: 10.1007/s11307-018-1234-7
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive PET Imaging of a Ga-68-Radiolabeled RRL-Derived Peptide in Hepatocarcinoma Murine Models

Abstract: Our study successfully prepared [Ga]DOTA-RRL with a high labeling yield under the optimized reaction conditions and demonstrated its potential role as a PET imaging agent for tumor-targeted diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In a first step, the benzylprotected podand GlyCAM(Bn) (14) was synthesized in a manner similar to that of Glu( t Bu)CAM(Bn) (10) according to the procedure of Dertz et al 55 In situ N-hydroxysuccinimide (NHS) activation of the arm Glu( t Bu)CAM(Bn) (10) with Nethyl-N′-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC•HCl) enabled further conjugation to the tris(2aminoethyl)amine backbone to yield the monosubstituted TREN intermediate 13. In situ NHS activation of the second arm, GlyCAM(Bn) (14), enabled conjugation to the two remaining primary amines of 13 and completion of the fully protected ligand (15). Simultaneous deprotection of the tertbutyl and benzyl groups under acidic conditions yielded the final ligand 4 that was kept under N 2 (g) in the dark at 4 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a first step, the benzylprotected podand GlyCAM(Bn) (14) was synthesized in a manner similar to that of Glu( t Bu)CAM(Bn) (10) according to the procedure of Dertz et al 55 In situ N-hydroxysuccinimide (NHS) activation of the arm Glu( t Bu)CAM(Bn) (10) with Nethyl-N′-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC•HCl) enabled further conjugation to the tris(2aminoethyl)amine backbone to yield the monosubstituted TREN intermediate 13. In situ NHS activation of the second arm, GlyCAM(Bn) (14), enabled conjugation to the two remaining primary amines of 13 and completion of the fully protected ligand (15). Simultaneous deprotection of the tertbutyl and benzyl groups under acidic conditions yielded the final ligand 4 that was kept under N 2 (g) in the dark at 4 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The volatiles were then removed under reduced pressure to yield TREN-Glu( t Bu)-CAM(Bn) (13) as a yellow paste (0.42 g, 91%) that was used immediately in the next step without further purification. 1 TREN-bisGlyGlu( t Bu)-CAM(Bn) (15). To a stirred solution of GlyCAM(Bn) (14, 0.27 g, 0.69 mmol) in anhydrous dichloromethane (10 mL) was added N-hydroxysuccinimide (NHS, 0.106 g, 0.921 mmol), and the resulting reaction mixture was cooled to 0 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in recent years, it has been found that the RRL peptide can also bind to a variety of tumor cells, such as HepG2, HT-1080, and PC-3 cells . Based on these results, our team started to develop RRL peptides, particularly 99m Tc-labeled radiopharmaceuticals. Tumor imaging and biodistribution demonstrated obvious 99m Tc-RRL uptake in the subcutaneous tumor models and pulmonary metastasis models . These findings implied that the RRL probe may present the valuable tumor accumulation performance, but the labeling yield needs to be improved.…”
Section: Introductionmentioning
confidence: 99%